Recent discoveries of oral substances’ effects on osteoporosis treatment - novel markers and pathways - Judek, Roksana; Latour, Emilia; Latour, Marianna; Melnyk, Bohdan; Rygielski, Artur (Quality in Sport, 2024)
The search for optimal osteoporosis treatments continues, as the medications currently used in clinical therapy carry a risk of rare but acute side effects. New knowledge about etiopathogenetic pathways and osteoporosis biomarkers enabled the exact examination of various oral substances, often previously recognised for their positive impact on bone mass growth. A cross-section of novel reports from this year on the applications of many orally administered substances is presented. Diet, gut microbiota aspect, functional food, diabetes drug – empagliflozin and a variety of substances known from Chinese traditional medicine are now characterized in the context of the possible mechanism of treating or preventing osteoporosis. The progress of bone mass density and quality-regulating pathways recognition led to the finding of multiple orally administered substances with favorable mediation properties. The precise diagnosis of the substances’ working mechanisms approves their potential use in new formulations of clinical treatments. Presently only used in diet supplementation, the orally administrated antiosteoporotic substances are potential core ingredients of modernized medications, provided their presumptive adverse effects are ruled out.